The Effect of Transformational Leadership, Work Motivation and Job Satisfaction on The Performance of BKKBN Employees Deputy for Advocacy Movement and Information - Muhammad Rizki Darmawan; Beureukat Beureukat; Melati Melati; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
This study aims to analyze the influence of transformational leadership, work motivation, and job satisfaction on the performance of BKKBN Deputy for Advocacy and Information Mobilization. This study uses primary data and secondary data by distributing questionnaires to 96 respondents. Multiple linear regression analysis technique was performed using SPSS 23 software. The results of this study indicate that transformational leadership (X1), work motivation (X2), and job satisfaction (X3) have a positive and significant impact on employee performance (Y). The results of the study show that transformational leadership (X1) has a positive and significant effect on employee performance (Y) with grades tcount > ttable (3.207 > 1.661) and value significance 0.002 which smaller of 0.05 (0.002 > 0.05). Work motivation has a positive and significant effect on employee performance (Y) with a value of tcount> ttable (3.246 > 1.661) and a significance value of 0.002 which is less than 0.05 (0.002 > 0.05). Job satisfaction (X3) has a positive and significant effect on employee performance (Y) with value tcount > ttable (7.886 > 1.661) and a significance value of 0.000 which is less than 0.05 (0.000 > 0.05).